2007
DOI: 10.1590/s0102-695x2007000400021
|View full text |Cite
|
Sign up to set email alerts
|

Controle farmacognóstico das raízes de Heteropteris aphrodisiaca O. Mach. (Malpighiaceae)

Abstract: Unitermos: Heteropteris aphrodisiaca, Malpighiaceae, "nó-de-cachorro", controle de qualidade farmacognóstico, CCD, CLAE, fl avonóides.ABSTRACT: "Pharmacognostic analysis of the roots of Heteropteris aphrodisiaca O. Mach. (Malpighiaceae)". The roots of Heteropteris aphrodisiaca, called "nó-de-cachorro" (dog-knot) for their morphological similarity to the canine penis, are used in popular medicine as an aphrodisiac or stimulant, and to treat dysentery. The objective of the present study was to characterize these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
10
0
7
Order By: Relevance
“…The phytochemical characterization of the BST0298 extract employed in the present study showed the presence of flavonoids astilbin, neoastilbin, and isoastilbin, well characterized (see Figure 1 and text in Material and Methods) and identified by HPLC, and an aliphatic nitro compound known as 2,3,4,6-tetra-O-(3-nitropropanoyl)-O-β-Dglucopyranoside (Roman Júnior et al, 2005;Marques et al, 2007). However, no positive effect of these flavonoids on memory has been reported in the literature.…”
Section: Discussionmentioning
confidence: 71%
“…The phytochemical characterization of the BST0298 extract employed in the present study showed the presence of flavonoids astilbin, neoastilbin, and isoastilbin, well characterized (see Figure 1 and text in Material and Methods) and identified by HPLC, and an aliphatic nitro compound known as 2,3,4,6-tetra-O-(3-nitropropanoyl)-O-β-Dglucopyranoside (Roman Júnior et al, 2005;Marques et al, 2007). However, no positive effect of these flavonoids on memory has been reported in the literature.…”
Section: Discussionmentioning
confidence: 71%
“…O estudo de plantas medicinais, sob o ponto de vista anatômico, revela-se de grande interesse, pois contribui para o controle de qualidade e a correta identificação de fármacos vegetais (Duarte & Menarim, 2006;Leite et al, 2007;Marques et al, 2007;Scopel et al, 2007;Mauro et al, 2008;Carpano et al, 2009;. Eugenia florida DC.…”
Section: Introductionunclassified
“…O controle de qualidade de plantas medicinais deve ser realizado e envolve análise sensorial macro e microscópica como primeira etapa para estabelecer a identificação e o grau de pureza da amostra analisada seguida de uma análise físico-química (Choi et al, 2002;Donato & Morretes, 2007;Marques et al, 2007;Barros & Teixeira, 2008;Budel & Duarte, 2008;Chaves & Costa, 2008;Del-Vechio-Vieira et al, 2008;Empinotti & Duarte, 2008;Paula et al, 2008;Marques et al, 2008;Mauro et al, 2008;Porto et al, 2008;Bueno & Bastos, 2009;Carpano et al, 2009;Gette et al, 2009;Gomes et al, 2009;. Requerimentos para segurança e eficácia do uso de produtos vegetais têm sido demonstrados (Bast et al, 2002;Silveira et al, 2008;Nascimento et al, 2009).…”
Section: Introductionunclassified